1161 Parental engagement and feedback on Parent Report of Children's' Abilities- Revised Questionnaire (PARCA-R-Q)- the ongoing Quality Improvement project. (17th August 2022) - Shekhar, Lipi; Merchant, Nazakat; Lasokova, Marika; Huertas-Ceballos, Ángela; Warren, Emma
Abstract : Aims: Standardised neurodevelopmental questionnaires offer an alternative to formal resource-intensive, face-to-face assessment for high-risk NICU graduates. PARCA-R-Q is a validated tool for assessing children's cognitive and language development at 24 months of age and is recommended by NICE, UK. Currently, there is no data on parental feedback on using this questionnaire. The aim is to gather service user feedback for PARCA-R-Q as a quality improvement and feasibility study. Methods: Formal multidisciplinary 2-year neurodevelopmental assessment clinic for infants at high risk for acquired brain injury currently runs in a hybrid model. All parents who completed PARCA-R-Q for this clinic were invited to participate in anonymised feedback. The survey consisted of open and closed-ended questions and explored parents' knowledge, language barriers, completion time and ease to complete the PARCA-R-Q. Parental views on the hybrid clinic model were explored. An electronic link to the feedback was sent after verbal consent. The survey was re-designed after a feasibility study done for the first 6 months Results: 31 parents completed the feedback, 14 in the feasibility study phase and 17 afterwards. 77% were preterm, 71% spoke English as their first language and 71% completed the PARCA-R-Q before attending the developmental clinic. 93% of the PARCA-R-Q was completed by mothers and 6.4% needed aid from healthcare professionals. 86% preferred face to face formal assessments. 84% thought the PARCA-R provided ideas encouraging their child's developmental growth. However, 45% thought that the questionnaire needs improvement and is only somewhat useful. Conclusion: The implementation of the PARCA-R questionnaire has been a positive change, empowering parents/guardians in the assessment of their child and providing them with ideas to boost the child's development. However, a significant number preferred face to face formal assessments. This is the first pilot data on parental feedback on the PARCA-R-Q. Further data with a larger cohort is needed to quantify the results.